[Abstract] The Nanaimo and Charles Camsell Indian Hospitals: First Nations' narratives of health care, 1945-1965 - Meijer Drees, Laurie (Histoire sociale / Social History, 2010)
Article abstract Abstract of an article written by Laurie Meijer Drees, "The Nanaimo and Charles Camsell Indian Hospitals: First Nations' Narratives of Health Care, 1945-1965" which appeared in the journal Histoire Sociale/Social History. https://viuspace.viu.ca/bitstream/handle/10613/3153/Abstract.pdf?sequence=5